2017
DOI: 10.1590/0102-311x00120816
|View full text |Cite
|
Sign up to set email alerts
|

Abuso de drogas e transtornos alimentares entre mulheres: sintomas de um mal-estar de gênero?

Abstract: The article discusses drug abuse and eating disorders from the critical gender and healthcare perspectives, postulating that subjective suffering can be expressed in the body through psychosomatic illnesses. From this perspective, craving for drugs or superfluous consumer goods, just as illness from self-imposed hunger in pursuit of an ideal of slimness, as in anorexia and bulimia, can be symptoms that expose the woman's suffering. A review in the fields of public health and feminist theories highlights the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
1
0
7
Order By: Relevance
“…Sem encontrar respaldo na falta de um quadro clínico característico (DUNSELMAN et al, 2014;JOHNSTON;REID;HUNTER, 2015;KENNEDY et al, 2005;PARAZZINI et al, 2017;SOLIMAN;FULDEORE;SNABES, 2017), os atrasos no diagnóstico da endometriose relacionam-se à naturalização dos sintomas pela sociedade em geral, incluindo os profissionais de saúde (BALLARD; LOWTON; WRIGHT, 2006). Ocorre que a ciência -em sua suposta neutralidade -não é inerte às práticas historicamente contingentes que atuam no contínuo processo de formação das performatividades de gênero (BUTLER, 2006;2011).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Sem encontrar respaldo na falta de um quadro clínico característico (DUNSELMAN et al, 2014;JOHNSTON;REID;HUNTER, 2015;KENNEDY et al, 2005;PARAZZINI et al, 2017;SOLIMAN;FULDEORE;SNABES, 2017), os atrasos no diagnóstico da endometriose relacionam-se à naturalização dos sintomas pela sociedade em geral, incluindo os profissionais de saúde (BALLARD; LOWTON; WRIGHT, 2006). Ocorre que a ciência -em sua suposta neutralidade -não é inerte às práticas historicamente contingentes que atuam no contínuo processo de formação das performatividades de gênero (BUTLER, 2006;2011).…”
Section: Discussionunclassified
“…A 5ª edição do Manual Diagnóstico e Estatístico de Transtornos Mentais (DSM), embora já mencione as questões de gênero, ainda justifica diferenças na saúde mental de homens e mulheres como associadas principalmente a fatores orgânicos e "eventos do ciclo reprodutivo ao longo da vida" (AMERICAN PSYCHIATRIC ASSOCIATION, 2014, p. 15). Além disso, ao trazer que "mulheres têm mais chances de confirmar um transtorno depressivo, bipolar ou de ansiedade e de fornecer uma lista de sintomas mais abrangente do que homens" (p. 15) sem problematizar esse dado estatístico, o DSM-V ignora os fenômenos socioculturais que permeiam a feminilidade em suas dimensões materiais e simbólicas (COELHO et al, 2009;SIMÕES-BARBOSA et al, 2017). O sofrimento e o funcionamento narcísico dos sujeitos são atravessados por valores de gênero, de modo que a "quebra psíquica" mais frequente em mulheres não é um evento não aleatório (ZANELLO; FIUZA; COSTA, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O consumo de substâncias psicoativas (SPA) sempre existiu ao longo do tempo, não se restringindo ao gênero masculino 1 . Atualmente, como agravante desse processo, a preservação da autoimagem relacionada ao preconceito e estigma social diante das mulheres que consomem SPA tem como consequência o uso escondido 1 e a demora na busca por tratamento.…”
Section: Introductionunclassified
“…3 It is known that there is a possibility that public policies do not contemplate the singularities of the female population using drugs, their specific use, as well as the differences in consumption and access to health services. 4 It is reported that, in response to the demand to meet users' health needs, substitutive services have emerged regarding drug abuse such as the Psychosocial Alcohol and Drug Attention Centers (CAPS AD). 5 The objective of this service is to serve the population according to its area of coverage, through clinical follow-up and promoting the social reintegration of users through access to work, leisure, the exercise of civil rights and the strengthening of ties with family and community.…”
mentioning
confidence: 99%